Design of displacement-based viscous damper damping structures - Shuo Dong; Wen Pan; Liaoyuan Ye; Jingwei Wang (Scientific Reports)
Abstract With the acceleration of modern urbanization, the height and density of buildings are increasing, and the need for seismic protection in structural design is becoming more and more urgent. The robust recovery, great reusability, and exceptional seismic performance of the viscous damper make it a popular choice for high-rise construction. To improve the seismic damping effect of the building structure, the study employs methodologies that the restoration force model simulates the viscous dampers’ resistance against the seismic forces, and the time course analysis method allows for analysis of the dynamic response of structures to seismic activities through time in realigning the position of the viscous damper. Furthermore, the study utilizes the multi-objective optimization method to optimize the distribution parameters of the damping structure, thereby enabling the design of a displacement-based vibration-damping structural configuration for the viscous damper. The results revealed that the maximum inter-story displacement angle produced by the studied seismic-damped structural design under five sets of natural seismic waves used for validation is 1/909, which is less than the displacement angle limit value of 1/1000, and meets the requirements of the Chinese code for seismic design of buildings (GB 50011 − 2010). In conclusion, the study of design for viscous dampers using displacements offers positive benefits with an inter-story displacement angle decrease of 41.93%, acceleration decrease of 16.27%, and layer displacement decrease of 6.72%. The conclusion would be useful for decision-making to give estimates of seismic losses during construction.